Lacertus Fibrosis versus Achilles Allograft reconstruction for Chronic Distal Biceps Tears: A Biomechanical Study. Issue 3 (24th March 2016) - Ramirez, Miguel; Murthi, Anand
Objectives: Chronic distal biceps tears can be difficult to treat as in many cases, the remaining biceps tendon is significantly retracted and an allograft may be required to provide length for reconstruction. The lacertus fibrosis (LF), being a local, stout, fibrous sheath, can potentially be used as a reconstruction graft, obviating the need for allograft tissue. The purpose of this study is to evaluate the strength of the lacertus fibrosis compared to achilles allograft (AA) for distal biceps reconstruction. Methods: 10 fresh-frozen matched cadaveric pairs of elbows were used in this study. The distal biceps tendon was isolated and 3 centimeters of tendon was resected. In Group 1, the LF was identified and released from its distal attachment, maintaining its attachment to the biceps muscle. This was then tubularized and repaired to the radius via button fixation. In Group 2, an AA tendon graft was sutured to the biceps muscle via Pulvertaft weave and similarly repaired to the ulna via button fixation. The prepared radii were rigidly mounted at a 45-degree angle in a MTS electromechanical test frame (MTS Systems, Eden Prairie, MN). The proximal biceps muscle was secured in a custom fabricated cryogenic grip and allowed to freeze for 60s prior to testing. Two differential variable reluctance transducers (DVRTs) were mounted on the specimens, one at the radius-soft tissue junction and the second in the muscle or muscle allograft tissue junction proximal to the repair. Specimens were then loaded at a displacement rate of 20 mm/min until failure. Failure was defined as a 3 mm displacement of the DVRT located at the radius-soft tissue junction. Stiffness was calculated from the initial linear portion of the load versus radial DVRT curve. A t-test was used to determine if any observed differences were significant (p≤0.05) Results: Load to failure, as defined as a 3mm gap formation by DVRT was similar between both groups. Load to failure in Group 1 (LF) was 20.17 ± 5.52 N versus 16.89 ±4.54 N in Group 2 (AA) (p=0.18). Stiffness of the construct was also not statistically different, with Group 1 (LF) averaging 12.32± 7.11 KPa versus 10.48 ± 5.66 KPa in Group 2 (AA) (p=0.34). Conclusion: Lacertus fibrosis reconstruction for chronic distal biceps tears was as strong biomechanically as the commonly used achilles tendon allograft in terms of load to failure and construct stiffness. This may be a reasonable alternative for chronic distal biceps reconstruction in which primary repair is not possible.